Field observations of the lethality characteristics of endangered and endemic fish under the stress of total dissolved gas supersaturation. (4th August 2020) - Yuan, Quan; Wang, Yuanming; Liang, Ruifeng; Feng, Jingjie; Li, Yong; An, Ruidong; Li, Kefeng
Abstract: Total dissolved gas supersaturation (TDGS) caused by high dam discharge may threaten the survival of fish downstream. This study investigated the TDGS of Dadu River in the first 3 years (2016–2018) after the operation of Dagangshan hydropower station. The effect of TDGS on endemic fish was also evaluated for the first time in this study. Schizothoracin prenanti, Schizothorax davidi and Leptobotia elongata, which are endangered and endemic species in the Dadu River, were selected to evaluate the adverse effects of supersaturation on fish. We found that the supersaturation level varied from 115% to 127% in 2016, from 111% to 121% in 2017, and from 103% to 112% in 2018. The average water levels in these 3 years were 2.99, 2.34 and 1.14 m, respectively. The mortality of fish was positively correlated with TDGS and negatively correlated with water depth. The mortality of juvenile fish was highest in 2016, and increased TDGS had a greater contribution to fish mortality than the other factors. The highest mortality of adults occurred in 2017, and inadequate water depth was an important factor that caused fish mortality. The lowest mortality of both adults and juveniles occurred in 2018, and gas bubble disease in fish was almost never found. Even at shallow water depths, low TDGS (103%–112%) did not cause fish mortality.